PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN SELF EfFICACY TERHADAP KOMITMEN ORGANISASI (PADA HOTEL GRAND ZURI PEKANBARU) - Fadila Malvika; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to analyze the transformational leadership style and effectiveness selff and its influence on organizational commitment at Grand Zuri Hotel Pekanbaru. Transformational leadership as a variable (X1), Selff Eficacy as a variable (X2), and Organizational Commitment as a variable (Y). Method in this research is descriptive and quantitative by using program of SPSS 21, where sample used is 89 employees conducted by census. Technical data through questionnaire The results of analysis using validity test, reliability test, determination test, simple linear regression test, multiple linear regression test, t test and F test can be concluded significant transformational leadership towards organizational commitment at Grand Zuri Hotel Pekanbaru, It can be concluded significant Self efficacy to organizational commitment at Grand Zuri Hotel Pekanbaru as well as transformational leadership and significant effectiveness towards organizational commitment at Grand Zuri Hotel Pekanbaru. Keywords: Transformational Leadership, Selff Effectiveness, Organizational Commitment.